Study of zinc oxide nanoparticles and zinc chloride toxicity to annelid Enchytraeus crypticus in modified agar-based media - Hrda, Katerina; Pouzar, Miloslav; Knotek, Petr (Environmental science and pollution research international, 2018)
Acute toxicity of zinc oxide nanoparticle (ZnO-NP, mean particle size diameter of 10 nm) powder and water-soluble salt of zinc (ZnCl2) to annelid Enchytraeus crypticus was tested using an agar-based nutrient-enriched medium with the addition of kaolin and humic acids (HA). Adults of the E. crypticus were cultivated in pure agar and in three types of modified exposure media containing different proportions of model soil constituents. Potworms were exposed to zinc in both forms (1-1000 mg kg-1 of agar) for 96 h. In experiments with ZnCl2, toxicity of zinc was the highest in pure agar followed by agar with HA and agar with kaolin and HA and the lowest toxicity was observed in agar with kaolin. The corresponding LC50 values were 13.2, 28.8, 39.4, and 75.4 mg kg-1 respectively. In contrast, zinc in the form of ZnO-NPs was most toxic in the presence of HA followed by pure agar, agar with kaolin, and kaolin with HA. In this case, LC50 values were 15.8, 43.5, 111, and 122 mg kg-1 respectively. Scanning electron microscopy revealed that the smallest agglomerates occurred in the presence of kaolin, where ZnO-NPs were sealed in a kaolin shell. This effect reduced the bioavailability and toxicity of the NPs. In contrast, larger agglomerates were observed in the presence of HA but a larger amount of zinc was dispersed in the volume of agar.
Keywords: oxid zinečnatý; Nanoparticles; Zinc Oxide; Chlorides; chloridy; Soil Pollutants; látky znečišťující půdu; agar; Kaolin; Interactions; zvířata; Agar-based cultivation media; kovové nanočástice; Physicochemical characteristics; Culture Media; Humic acids; testy akutní toxicity; kultivační média; sloučeniny zinku; Animals; Worms; Zinc Compounds; Agar; Metal Nanoparticles; Oligochaeta; Toxicity Tests, Acute